Load Variation Analysis Of Generator On Lembar-Padang Bai Ro-Ro Ships For Safety Maritime - Haryanti Rivai; Baharuddin; M. Rusydi Alwi; Muhammad Iqbal Nikmatullah; Masyhuri Damis (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2025)
A generator is vital for ship operations, serving as a source of electrical power generation on board. The electrical system changing loads every second. Even with these changes, the power demand stays steady and must be supplied correctly. Voltage stability shows how well the system can keep the voltage steady during normal operation or after something goes wrong. Things like added loads or changes in the system setup can also affect this stability. The method used in this research is circuit modeling that conducted using the Electrical Transient Analysis Program (ETAP) software to collect data. This modeling is essential for designing a system that can be effectively simulated. The result is the voltage and frequency stability values while the air compressor motor operates at 4.5kW showed no significant voltage changes. In contrast, when the electric bow thruster motor, operating at 335kW, runs, the voltage dropped to 85% within 6.5 seconds. During a short circuit at the 15th second compartment bus, the engine room bus experiences a voltage dropped of 77%, while the hull compartment bus dropped by 45%. This showed that the system is unsafe for the equipment, as the as a voltage.